PEMBERDAYAAN PEREMPUAN OLEH BP3TKI PADA KELOMPOK PMI PURNA SUMBER REJEKI DESA RASAU JAYA TIGA KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA - Erica Uli; Rustiyarso Rustiyarso; Riama Al Hidayah (Universitas Tanjungpura, 2022)
AbstractThe purpose of the study was to determine the empowerment of women in the PMI PurnaSumber Rejeki group by BP3TKI in Rasau Jaya Tiga Village, Rasau Jaya District, KubuRaya Regency. The research approach used is a descriptive qualitative approach. Datacollection techniques in the form of observation, interviews, and documentationı. Thedata collection tools used observation guides, interview guides, and documentationı.Data analysis techniques are data reduction, data presentation and drawingconclusions. Research analysis is presented descriptively using 4 informants. Theresults of the research show that training and mentoring activities have been carriedout. It is proven that there are technical training activities to make corn-basedpreparations which were held by BP3TKI for 6 days. Once every 3 months by BP3TKIIn mentoring BP3TKI carries out the role of consultant and facilitator for the PMIPurna Sumber Rejeki group, although training and mentoring activities are strictlycarried out by BP3TKI. Not a few members left and the PMI Purna Sumber Rejek groupwhile the group was running. Of course, this became a challenge in maintaining theempowerment of women from the PMI Purna Sumber Rejek group in Rasau Jaya VillageTiga Kecanatan Rasau Jaya, Kubu Paya RegencyKeywords: BP3TKI, PMI, Women Empowerment